Improvement of safety of autonomous electrical installations by implementing a method for calculating the electrolytic grounding electrodes parameters - Budanov, Pavlo; Brovko, Kostiantyn; Cherniuk, Artem; Pantielieieva, Iryna; Oliynyk, Yuliya; Shmatko, Nataliia; Vasyuchenko, Pavlo (Eastern-European Journal of Enterprise Technologies, 2018)
We have solved the task of safety improvement in the grounding process of autonomous mobile electrical installations. Existing procedures for the calculation of normalized resistance of grounding electrodes in electric installations have been examined and studied. Their main drawbacks have been revealed: the difficulty and complexity of calculations; the probabilistic and approximate character; the use of source data taken to calculate the electrophysical parameters of stationary grounding electrodes; the calculations do not account for the structural-phase structure of soil and the volume of electrolyte. Based on the application of percolation theory and the apparatus of fractal-cluster geometry, we have modeled the process of electrolytic grounding in heterogeneous soils of different porous structure, which possess the percolation and fractal properties. A physical model of the process of electrolytic grounding has been developed, which takes into consideration the soil structure properties when changing the fractal dimensionality of a cluster over a certain range that forms the electrolytic grounding conductor with the normalized resistance. It has been shown that the model of conductivity of the electrolytic grounding electrode is defined by the soil electrical conductivity in a percolation channel of the porous structure of soil and can be considered as a function of the volumetric concentration of the electrolyte and the size of the volumetric structure of the electrolytic percolation cluster. We have derived analytical expressions to relate the normalized resistance of electrolytic grounding conductors and the specific resistivity of soil to the fractal dimensionality, volume of the electrolyte, the number of pores to the electrolyte, density of a geometrical volumetric body. We have improved a method for calculating the electrophysical parameters of electrolytic grounding conductors, based on accounting for the main linear size of the cluster of an electrolytic volumetric body, which coincides with the electrolyte penetration depth for various soil structures. We have established conditions for conductivity of the electrolytic grounding conductor in order to ensure safety during operation of the autonomous mobile electrical installation